PELATIHAN PERCAKAPAN BAHASA INGGRIS UNTUK PERKANTORAN PANTI ASUHANBANI ADAM AS MEDAN, SUMATERA UTARA - Andini Nur Bahri; Irma Yusriani Simamor; Fatma Yulia (Universitas Islam Negeri Sumatera Utara, 2022)
Orphans need support and attention more from stakeholders in order to improve their life skill. Some training and workshop should be conducted such as English and Computer. Bani Adam orphanage is one of the left behind orphanage in Medan which has insufficient facilities for the education of the orphans. They also rarely accepted any program that create the orphans capacities. This community service aim to increase the English skill of the orphans especially English for office to encourage the orphans gain better understanding in English for office.